Trend Perkembangan Islam di Indonesia : Suatu Pendekatan Teologis - Fauzan Saleh (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2002)
Islam is a part of the Indonesian history journey, at least since the 14th century when Islam had started rising in this country. The Islamic development in Indonesia as a part of the great mainstream which build the character of nation, has the high fluctuation describing the specific dynamic. It is also similar with the fact that the spread of Islam in some regions in Indonesia is not always in the same intensity. In certain regions, Islam spreads easily and dominates the culture oftheir society, while in other regions it doesn't dominate their culture whose the strong root of their people life pattern. It has been accepted incompletely form or just be a supplement of dominant culture. The trend of Islamic rising is so determined by the people understanding toward their religion doctrines. However, besides the social, politic and culture factors, the source of understanding the doctrine correctly often become the de scription of the religious society quality. Hence, in the course of time, the Islamic rising faces more complex challenges and needs to be observed more. This paper explores the general description of Islamic rising in Indonesia and the trend of rising in post reformation era.